Perumusan Kebijakan Publik dalam Menggali Akar Kemiskinan - Slamet Rosyadi; Tobirin ' (Universitas Riau, 2010)
The objective of this research was to identify and analyze deeply various poverty rootsof problem developing in both coastal and agriculture area as basis of formulating public policy inpoverty alleviation. Qualitative with multicase study method was applied in two villages in order togain complete description concerning roots of rural poverty. In-depth interview and observationwere used to collect qualitative data. Informants taken from farmer and fisherman leading actors,development agencies from district to village level, and other community organization actors werepurposively selected followed by snow-ball sampling in order to get more comprehensive data.Data was analyzed by interactive model consisting of interactive activities from data collection,reduction, display and verification/conclusion drawing. Results of this study show that roots ofpoverty in coastal villages are more complicated than those of agriculture one. This circumstanceindicates that coastal village area is the primary pocket of poverty. Some causes of poverty thatshould be paid attention by policy makers are low of education level, disadvantage developmentpolicy and marketing system for farmers as well as fishermen, and degraded coastal environment.Therefore, developmental efforts aimed at alleviating the poverty should be directed to improvethe primary roots of poverty problem.